Fasting Plasma Glucose Concentration in Relation to Nutritional Status Indicator and Physical Activity Level among Schizophrenia Patient - Della MW Cintakaweni; Saptawati Bardosono; Hervita Diatri (World Nutrition Journal, 2018)
Diabetes mellitus is often accompanied to schizophrenia patient. This condition probably related to genetic, antipsychotic drugs and the development of schizophrenia that can lead to an unhealthy lifestyle, such as sedentary lifestyle and the increased of dietary intake. Cross-sectional study was held in Psychiatry Department Cipto Mangunkusumo Hospital during May to June 2014 to determine the correlation between fasting plasma glucose concentration in schizophrenia patient to their nutritional status indicator and physical activity level. Forty-seven subjects finished the study protocol. The result showed that the fasting plasma glucose concentration in schizophrenia patient has no correlation with nutritional status indicator and physical activity level, in which 91.5% subject had normal fasting plasma glucose. However, there is a need for further investigation because 31.9% subject was overweight, 48.9% subject was obesity and 74.5% subject had central obesity.